Expanding the SRI domain family: A common scaffold for binding the phosphorylated C‐terminal domain of RNA polymerase II. Issue 23 (18th October 2014) - Rebehmed, Joseph; Revy, Patrick; Faure, Guilhem; de Villartay, Jean-Pierre; Callebaut, Isabelle
Abstract : The SRI domain is a small three‐helix domain originally discovered near the C‐terminus of both histone methyltransferase SETD2 and helicase RECQL5. The SRI domain binds to the C‐terminal repeat domain of the largest subunit of RNA polymerase II, allowing SETD2 and RECQL5 to regulate various mechanisms associated with RNA transcription. Using original tools to detect common patterns in distantly related sequences, we have identified SRI domains in several additional proteins, most of which are involved in RNA metabolism. Combining sequence analysis with structural prediction, we show that this domain family is more diverse than previously thought and we predict critical structural and functional features. Abstract : SRI domains bind to the phosphorylated C‐terminal domain of RNA polymerase II. Several novel members of the family are detected here. These members are involved in various mechanisms associated with RNA transcription. Analysis of the expanded family allows prediction of critical structural and functional features.